Integrating Electronic Information and Transaction Law (UU ITE) and Islamic Criminal Law: Addressing Malware-Based Data Theft - Apipuddin, Apipuddin; Nasri, Ulyan; Mulyohadi, R. Arif; Muslim, Asbullah (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study examines the phenomenon of information theft using malware, analyzed through the lens of Indonesian criminal law under Law No. 19 of 2016 on Electronic Information and Transactions (UU ITE) and Islamic criminal law principles. The research focuses on the legal implications and measures to address cybercrime, particularly data theft, in the digital era. Employing a normative juridical approach, the study analyzes primary and secondary legal materials, including statutory provisions, case laws, and relevant literature. Findings reveal that UU ITE provides detailed mechanisms for criminalizing and penalizing perpetrators of malware-based data theft, emphasizing preventive and repressive actions. From the perspective of Islamic criminal law, such acts are categorized under ta’zīr punishments, as they harm individuals and society by violating the principles of amanah (trust) and maslahah (public interest). The study concludes that while UU ITE effectively addresses cybercrime, integrating Islamic legal principles could enhance the ethical foundation of law enforcement, fostering a balanced approach between punitive measures and moral guidance. This research contributes to the discourse on harmonizing modern legal frameworks with religious values to strengthen cybersecurity law enforcement.